The performance of mengkuang leaf fiber reinforced low density polyethylene composites - N. A., Halim; Siregar, J. P.; Mathivanan, D.; Bachtiar, Dandi; Z., Ghazalli; M. R. M., Rejab; Tezara, C. (Faculty Mechanical Engineering, UMP, 2018)
The performance of mengkuang leaf fiber (MLF) reinforced low density polyethylene (LDPE) composites with different fiber volume and different mesh sizes were studied. The fibre weight percentage used in the research were 10%, 20%, and 30% and for different fiber size were <0.5 mm, 0.5-1 mm, and 1-2 mm. The extrusion and hot compression molding were used to fabricate the specimen testing. The mechanical testing performed were impact and flexural test which follows the ASTM standards D790-10 and Izod D256. It was observed that by increasing the fiber volume and fiber size, the flexural strength and the flexural modulus were increased. However the impact strength shows different results for fiber length and fibre content where the impact strength increases with fibre length but decreases with the increase of fiber content. It can be concluded that the 30% fibre content is the optimum fibre loading for the MLFLDPE composite with the flexural strength of 12.31 MPa, flexural modulus of 378.88 MPa and impact strength of 589.86 J/m whereby the 1.0-2.0 mm fibre length is the best fibre size for the MLF-LDPE composite with the flexural strength of 12.86 MPa, flexural modulus of 267.76 MPa and impact strength of 1511.57 J/m. In future studies fibres should undergo surface modification to increase the available surface area for reaction to increase the strength of the composite by better mechanical interlocking.